Persistent Wrinkles and Folds of Clothes - Kim, Byung-Cheol; Oh, Seungwoo; Wohn, Kwangyun (International Journal of Virtual Reality, 2011)
We present a novel approach to woven-cloth simu-lation in order to generate persistent wrinkles and folds. For a couple of decades, our community has identified and mimicked non-linear buckling of cloth based on the mechanical measure-ment of cloth. It has, however, scarcely paid attention to another important aspect of the measurement, the hysteresis of cloth be-haviors, which is the lag of the amount of forces between stress and relaxation. Our interpretation of the measurement indicates that persistent wrinkles and folds develop in part from the hyste-resis of cloth and its associated energy loss. Thus, we establish an adaptive energy model which takes stiffness coefficients and rest posture values not as constants but as variables over time and behavior. As stiffness coefficients and rest posture values change in proportion to the amount of the energy loss, they appear as persistent wrinkles and folds. Consequently, the clothes simulated by our method bring more realism with respect to visual identi-fication for past behaviors of cloth.